STIMULASI KETERAMPILAN ARGUMENTASI MAHASISWA CALON GURU BIOLOGI MENGGUNAKAN VARIASI PERTANYAAN DALAM GRUP DISKUSI FACEBOOK - Afandi, Afandi; Akhyar, M.; Suryani, Nunuk; Sadjidan, M. (978-602-7561-566)
In the context of online learning environments, the argumentation skill becomes an important priority for sustained engagement of students in productive negotiation of ideas and evidence based reasoning (Siakidou, Papadouris, & Constantinou, 2014). The aim of this study is to reveal the quality of argumentation skills stimulation used a variety of questions in Facebook group discussion for Biology student teachers. The method of this work was using quasi experiment with time series design. This study involved 24 Biology student teachers who contacted in online and expressed willingness to take part in Facebook group discussions. Results indicate that divergence questions types have a greater influence on the argumentation skills quantity rather than focal and brainstorming questions types, while the focal question types have a greater influence on the quantity of argumentation skills rather than brainstorming questions types. In addition, this study shows that brainstorming questions types (FA) have a better effect to coding scheme for individual arguments rather than focal questions types (NFA) and the divergent questions types (NJA) to stimulating the quality of argumentation skills of Biology student teachers. Further research to uncover the effect of topic discussion on the arguments quality is expected to enrich the findings in this study.Â Keyword: Argumentation skills stimulation, variety of questions, Facebook group discussionÂ